Continuity of activities for railway undertaking - Rozová, Dana; Šustr, Martin; Šohajek, Petr (Kaunas University of Technology, 2019)
The proactive approach is a way how to improve planning during crisis situations. The implementation of the Business Continuity Management System can improve planning process in the transport branch during the crisis situation in the affected area. During the selection of the method for business continuity is important to take into account the fact that this method must cover all the aspects of activities, must be easy to understand to evaluators and last but not least this method must provide the required outputs for evaluation.
Kontinuita činností subjektu železniční dopravy
Keywords: Continuity of activity; Railway transport; Railway undertaking; Kontinuita činností; železniční doprava; železniční podnik